Construction of new fluorophores by Diels-Alder reaction of diacenaphthothiophenes. Issue 38 (21st September 2017) - Yamamoto, Yuma; Fukuoka, Yoshiaki; Nishida, Jun-ichi; Kitamura, Chitoshi; Kawase, Takeshi
Abstract: The Diels–Alder (DA) reaction of diacenaphtheno[1, 2- b ;1′, 2′- d ]thiophene (1a ) with benzyne affords 1:1 and 1:2 adducts, 7 and8, in 47 and 11% yields. An X-ray crystallographic analysis reveals that8 possesses a dibenzobarrelene structure involving a rigid di(1-naphthyl)ethene moiety. Thus, the second DA reaction occurs at the central benzene ring of7 selectively. The 1:2 adduct8 emits intense blue fluorescence in CH2 Cl2 . Moreover, we examined the DA reactions of1a and tetra- t -butyl derivative1b with p -benzoquinone to afford acenaphtheno[1, 2- j ]fluoranthene10a, and its tetra- t -butyl derivative10b and a quinone11b, respectively. Novel fragmentation reaction should occur to produce the acenaphthenofluoranthene frameworks of10 . An X-ray crystallographic analysis reveals a rather planar structure of11b . The central benzene ring of11b shows large bond alternation by the Mills-Nixon effect. The compounds10a and10b emit sky blue fluorescence with moderate Φ SN values. The electronic properties of new compounds are well consistent with the theoretical predictions. Graphical abstract: